Knowledge, Attitude and Awareness about Inflation Crisis: Perceptions, Challenges and Coping - Chandana, Dr. K. Siri; Pratap, Dr. K. V. N. R.; Padma, Dr. T. Madhavi; Singh, Dr. Surbhit; Srujan Kumar, Dr. V. (International Research in Medical and Health Sciences, 2025)
This study explored the perceptions, challenges, and coping strategies adopted by students at Iligan Medical Center College (IMCC) amidst the ongoing inflation crisis. Employing a qualitative research approach, 40 students participated in in-depth interviews, providing rich insights into their lived experiences. Students overwhelmingly expressed concern and frustration towards the rising costs of essential goods and services. They perceived inflation as a significant threat to their financial well-being, jeopardizing their ability to afford basic necessities like food, transportation, and education. Many felt a sense of powerlessness and uncertainty about their future, particularly regarding their ability to complete their studies. The research identified several key challenges faced by students due to inflation. Affordability of food emerged as a major concern, with participants resorting to skipping meals, compromising on quality, or relying heavily on subsidized meals. Transportation costs also posed a significant burden, limiting mobility and access to educational resources. Additionally, the rising cost of academic materials like textbook and internet access further strained their finances, hindering academic performance. Despite the challenges, students exhibited remarkable resilience and resourcefulness in navigating the crisis. They can adjust spending habits by prioritizing essential needs, cutting back on non-essentials like entertainment and leisure, and adopting frugal practices like buying second-hand goods or sharing resources. By seeking financial assistance, many sought help from family, friends, or student loan programs to bridge the financial gap. Some explored part-time job opportunities, despite the added pressure on their academic schedule. Lastly, by utilizing campus support services the participants highlighted the importance of institutional support, such as subsidized meals, scholarships, and mental health resources, in mitigating the impact of inflation. The study concluded that inflation significantly impacts students’ lives, posing financial and emotional challenges that can hinder their academic success and overall well-being. However, students demonstrate remarkable adaptability and resilience in coping with the crisis. The findings emphasize the need for targeted interventions from educational institutions and policymakers aimed at alleviating the financial burden on students and ensuring their access to quality education during challenging economic times. Aim: To assess the level of understanding of inflation crisis: perceptions, challenges, and coping understanding strategies among undergraduate dental students in Khammam Objectives To determine the knowledge, attitude, and awareness about inflation crisis: perceptions, challenges, and coping strategies among undergraduate dental students based on gender. To determine the knowledge, attitude, and awareness about inflation crisis: perceptions, challenges, and coping strategies among undergraduate dental students based on year of students. Method: A cross-sectional survey was conducted among 200 dental students, comprising 63 males (31.5%) and 137 females (68.5%), including 44 first-year BDS students,54 second-year BDS students,34 third-year BDS students, 38 final-year BDS students, and 30 interns. The Survey included 12 questions exploring knowledge attitudes and awareness about the inflation crisis; perceptions, challenges, and coping strategies among undergraduate dental students based on gender and year of study using chi-square tests to identify statistically significant differences.